2020
DOI: 10.3390/medicina56100521
|View full text |Cite
|
Sign up to set email alerts
|

Positive Anti-SSA/Ro Antibody in a Woman with SARS-CoV-2 Infection Using Immunophenotyping: A Case Report

Abstract: The clinical spectrum of novel coronavirus infection appears to be wide, encompassing asymptomatic infection, mild upper respiratory tract illness, and severe viral pneumonia, with respiratory failure and even death. Autoantibodies, especially antiphospholipid antibodies, can occur in severe infections. Other autoantibodies are seldom reported. Here, a 60-year-old female patient without dry-mouth symptoms detected positive for anti-60 kDa SSA/Ro antibodies on day 43 after severe acute respiratory syndrome coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…A vasculitis is defined as secondary when blood vessel inflammation is a result of underlying disease or exposure to medications and/or infections like hepatitis B and tuberculosis [ 2 ]. Recent studies have shown that the novel coronavirus disease (COVID-19) has the potential to induce secondary vasculitis in patients [ 3 , 4 ]. Pathogenesis surrounding COVID-19-induced secondary vasculitis is still uncertain, however some researchers have hypothesized a cross-reactivity between SARS-CoV-2 antigen and autoantibodies in autoimmune disease [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A vasculitis is defined as secondary when blood vessel inflammation is a result of underlying disease or exposure to medications and/or infections like hepatitis B and tuberculosis [ 2 ]. Recent studies have shown that the novel coronavirus disease (COVID-19) has the potential to induce secondary vasculitis in patients [ 3 , 4 ]. Pathogenesis surrounding COVID-19-induced secondary vasculitis is still uncertain, however some researchers have hypothesized a cross-reactivity between SARS-CoV-2 antigen and autoantibodies in autoimmune disease [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…COVID -19 is an infectious disease with a strong inflammatory response as demonstrated by the phenomenon of “cytokines storm” [ 7 ]; therefore, it is intriguing to speculate that the reports on positive SSA antibodies in these patients [ 8 , 9 ] may indicate the existence of autoimmune inflammatory response similar to the one described in Sjogren’s syndrome [ 10 , 11 ] that can result in dry mouth as well.…”
mentioning
confidence: 99%
“…Además, cabe mencionar la positividad de los autoanticuerpos antinucleares extraíbles de tipo SSA (anti-Ro60). La elevación de los niveles de autoanticuerpos anti-Ro se ha descrito tras la infección por el SARS-CoV-2 [ 2 , 3 ]. Adicionalmente, se ha detallado el aumento de los valores de diferentes marcadores de autoinmunidad (factor reumatoide, anticuerpos anti-Ro y anticuerpos anti-SSB) tras la infección por el SARS-CoV-2 en pacientes afectos de enfermedades reumatológicas [ 4 ].…”
Section: Discussionunclassified